Nuclear magnetic resonance in hypertrophic cardiomyopathy. Issue 1 (July 1985) - Been, M; Kean, D; Smith, M A; Douglas, R H; Best, J J; Muir, A L
Abstract : The large differences in the spin lattice relaxation times (T1) of blood and myocardium (measured by nuclear magnetic resonance) allow the heart to be visualised without the use of contrast media. The findings using nuclear magnetic resonance in 11 unselected patients with hypertrophic cardiomyopathy were compared with those in equal numbers of normal subjects and patients with electrocardiographic features of left ventricular hypertrophy. In patients with hypertrophic cardiomyopathy characteristic septal hypertrophy was noted together with variable and sometimes pronounced hypertrophy of the left ventricular free wall, which is consistent with the heterogeneous nature of this disease. The mean (SD) ratio of septal to free wall thickness was 1.5(0.8) for patients with hypertrophic cardiomyopathy, 0.8(0.2) for those with left ventricular hypertrophy, and 0.9(0.2) for normal subjects. Although septal measurements by nuclear magnetic resonance were greater than those obtained by echocardiography there was a significant correlation between the two. Septal and free wall area were significantly smaller in normal subjects. There were no differences in septal or free wall T1 values between the three groups. Non-gated nuclear magnetic resonance can detect septal and free wall hypertrophy. With the addition of multiple slice acquisition, rapid estimation of myocardial mass will be possible allowing the potentially important assessment of progression or regression of myocardial hypertrophy.